Effect of a Web-Based Management Guide on Risk Factors in Patients with Type 2 Diabetes and Diabetic Kidney Disease: A JADE Randomized Clinical Trial - Chan, Juliana C. N.; Thewjitcharoen, Yotsapon; Nguyen, Thy Khue; Tan, Alexander; Chia, Yook Chin *; Hwu, Chii-Min; Jian, Du; Himathongkam, Thep; Wong, Kim-Leng; Choi, Yun Mi; Mirasol, Roberto; Mafauzy, Mohamed; et al. (American Medical Association, 2022)
Importance: Diabetic kidney disease (DKD) and its comorbidities can be prevented by treating multiple targets. Technology-assisted team-based care with regular feedback and patient empowerment can improve the attainment of multiple targets and clinical outcomes in patients with type 2 diabetes, but the effects of this intervention on patients with DKD are unclear.